pH And Antibiofilm Analysis Of Elephant Ginger (Zingiber Officinale Var. Officinale) Mouthwash Formulations Against Streptococcus Mutans – An In Vitro Study - Fibryanto, Eko; Stefani, Rosita; Santoso, Lidia (Faculty of Dentistry, Universitas Islam Sultan Agung, 2025)
Background: Caries is the most common oral disease. Streptococcus mutans is the main microorganism in caries etiology due to its ability to form biofilm. Biofilm can be eliminated using mouthwash. Elephant ginger (Zingiber officinale var. officinale) can be developed as a herbal mouthwash because it is able to inhibit S. mutans. This study aimed to analyze pH and antibiofilm effect in vitro of elephant ginger mouthwash formulations on S. mutans. Method: Elephant ginger was macerated with 96% ethanol, then formulated into 2.5%, 5%, 10%, and 15% mouthwash formulations, underwent pH measurement for 28 days, and their antibiofilm effect on S. mutans were measured using microplate reader for 1h (therapeutic assay) and 24h (preventive assay). Result: All formulations showed pH values ranging from 6.42-6.87, changing significantly within 28 days. All formulations were able to reduce S. mutans biofilm adherence for 1h better than commercialized herbal mouthwash and similar to 0.1% CHX. Furthermore, 5% and 10% mouthwash formulations showed similar effectivity to 0.1% CHX and commercialized herbal mouthwash in inhibiting S. mutans biofilm formation for 24h, while 15% mouthwash formulation was more effective than 0.1% CHX and similar to commercialized herbal mouthwash, and 2.5% mouthwash formulation was less effective than 0.1% CHX and commercialized herbal mouthwash. Conclusion: Elephant ginger mouthwash formulations showed pH values that were likely to decrease for 28 days and had the potential as an herbal mouthwash due to its antibiofilm effect on S. mutans.